Molecular and Biochemical Characterization of a Type II Thioesterase From the Zoonotic Protozoan Parasite Cryptosporidium parvum - Guo, Fengguang; Zhang, Haili; Eltahan, Rana; Zhu, Guan (Frontiers in Cellular and Infection Microbiology, 2019)
Cryptosporidium parvum is a globally important zoonotic parasite capable of causing severe to deadly diarrhea in humans and animals. Its small genome (~9.1 Mb) encodes not only a highly streamlined metabolism, but also a 25-kb, 3-module fatty acid synthase (CpFAS1) and a 40-kb, 7-module polyketide synthase (CpPKS1). The two megasynthases contain a C-terminal reductase domain to release the final products with predicted chain lengths of ≥C22 for CpFAS1 or C28 to C38 for CpPKS1. However, the parasite genome also encodes a discrete thioesterase ortholog, which raises a question on whether the parasite uses this thioesterase as an alternative tool to release the final products from CpFAS1 and/or CpPKS1, as an editor to remove nonreactive residues or aberrant intermediates, or to control starter units as seen in other organisms. In the present study, we have confirmed that this C. parvum thioesterase is a type II thioesterase (thus named as CpTEII). CpTEII contains motifs and catalytic triad characteristic to the family of type II thioesterase family. CpTEII is a cytosolic protein expressed during the entire parasite life cycle stages, and it prefers to hydrolyzing medium chain fatty acyl thioesters, i.e., C6:0 to C12:0 fatty acyl-CoAs with the highest activity towards C10 decanoyl-CoA. These observations suggest that CpTEII may mainly act as an editor to remove nonreactive residues and/or aberrant medium acyl chain from CpFAS1 and/or CpPKS1. However, CpTEII also displays a low activity on C22:0 docosanoyl-CoA, implying its possible ability to release the final product from CpFAS1.